Strategi Komunikasi Pemasaran Dalam Meningkatkan Brand Awareness (Studi Kasus pada Susu Kemasan di akun Instagram Dancow versi Hari Ibu) - Pranasa, Risyaf Kudus (Universitas Bumigora, 2023)
In a marketing communication various kinds of strategies are often used, starting from the selection of a character who is considered capable of conveying a message, both visible and invisible. Media selection is also an important thing to make a choice before determining the audience or to whom the message will be delivered. In the current digital era, Instagram is often the choice to be used as a medium in promoting a product or campaigning for advertisements for goods or services. Dancow is a company selling goods in the form of children's milk that uses social media to build its brand awareness. In building a marketing communication strategy packaged in a poster or picture, Dancow has a strong character. Starting from the selection of yellow which is very prominent and strong as the distinctive color of its product, Dancow. In addition to choosing yellow, Dancow also chose a female figure, in this case the mother, to be the central figure in his poster. The figure of a mother is considered to represent a feeling of affection which is packaged attractively. The use of the pronoun child to baby also often appears in the picture shown. The use of this pronoun also seems to convey that Dancow has a different way of conveying messages to his followers.